Evaluation of plastic crate as replacement for raffia basket to prevent in-transit damage of packaged tomatoes - Babarinsa, F A; Ogundele, R B; Babarinsa, O A; Omodara, M A (Journal of Postharvest Technology, 2018)
In-transit damage of tomatoes packaged in plastic crate and raffia basket was evaluated in cross- regional transportation trials undertaken from Kwana Garfan (in Kano State) to Mile 12 market (in Lagos), Nigeria. Roma tomatoes were purchased from farmers and aggregated at a collection centre located at Kwana Garfan. There, two 25-tonne trucks were loaded with wholesome tomatoes differently packaged in plastic crate and raffia basket. Before departure to Lagos, samples of each filled container type were strategically positioned on the respective trucks. The commercial trips (from Kwana Garfan to Mile 12) covered a distance of 998 km, taking two (2) days. At Mile 12 market (Lagos destination), in-transit damage in delivered tomatoes was evaluated by sorting and separating damaged fruit within sample lots of each container type. Weights of damaged fruit in each sample container were determined for each truck. Baskets incurred high in-transit damage of 34.72% to 49.78% (with 41.12% average). The use of plastic crate reduced this damage to a level of 4.69 to 5.24% (with 4.92% average), thereby reducing damage in crates by 88%. In trucks, loaded in 5 basket layers, high levels, 49.78% and 45.70%, of the total damage occurred at the bottom and topmost layers (first and fifth layers respectively) of tomato baskets while lower damage levels of 37.4%, 36.72% and 37.9% occurred at the three middle layers (second, third and fourth layers) respectively. A follow-up trial with a 20-tonne truck carrying baskets of tomatoes from Kaduna showed the same trend of fruit damage.